Políticas públicas de arquivo: a gestão documental do arquivo público do estado do Espírito Santo - Luiz Carlos da Silva (2013)
Innovations experienced in the Public Archives of the State of Espírito Santo (APEES) provoked the interest in inquiring and researching about the public archive policies, responsible for the transformations occurred, and which led to changes we found in the document management environment. We describe what decisions of public archive policies are adopted, configured as document management which boost the quality of archival information in the governmental scope, in order to obtain positive results for the government and the society. We use the dissertation toacquire answers on these inquiries, because we believe that the public archive policies subsidize the administration and society, contributing to transparency and guarantee the citizens' rights, the governance and the democratic exercise of power. This study is conducted in the fields of common interests between Archivology and Information Science, for the importance of document management as an effective tool to the flow of social information. We use the method of documentary research that will provide knowledge about the problem of research and to deepen in theissues we appealed to bibliographic databases. We also use the technique of partially structured interviews, by addressing particularized issues and by using open questions to subsidize the subjective gaps not answered by documentary research. We present in the research the interrelation between the Archival Information and the Archive Documents, using as beacons the theoretical studies of Silva (2008), Jardim(1999) and Campillos (1996). An analysis of the concept of "public policy"through a holistic view (Policy, Public Policy, Information Policy and Public Archive Policy) was developed for a better understanding of the research proposal, from the authors: Pereira (2009), Souza (2006), Silva (2008) Jardim (2006, 2011). The public policy cycle was performed with the conclusion in the reprogramming. The APEES presented through decision matrices solutions with prior elements for the successfulresumption of the new cycle. We detected some inconsistencies that were presented as suggestions to contribute to the improvements in document management in attending the social demands.